2018
DOI: 10.1177/0895904818755468
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Characteristics and Student Learning in Mathematics: A Comprehensive Assessment

Abstract: Diverse stakeholders have an interest in understanding how teacher characteristics—their preparation and experience, knowledge, and mind-sets and habits—relate to students’ outcomes in mathematics. Past research has extensively explored this issue but often examined each characteristic in isolation. Drawing on data from roughly 300 fourth- and fifth-grade teachers, we attend to multiple teacher characteristics and find that experience, knowledge, effort invested in noninstructional activities, and participatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 73 publications
2
33
1
2
Order By: Relevance
“…Consistent with previous studies (e.g., Clotfelter et al, 2006Clotfelter et al, , 2010Hanushek and Rivkin, 2006;Hill et al, 2019), we found evidence for teacher sorting with certified and more experienced teachers working in urban public than rural public schools. The exception to this rule in our study is the greater proportion of certified teachers in public schools compared to private schools.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous studies (e.g., Clotfelter et al, 2006Clotfelter et al, , 2010Hanushek and Rivkin, 2006;Hill et al, 2019), we found evidence for teacher sorting with certified and more experienced teachers working in urban public than rural public schools. The exception to this rule in our study is the greater proportion of certified teachers in public schools compared to private schools.…”
Section: Discussionsupporting
confidence: 91%
“…While there is no policy in Ghana that deliberately assigns teachers and students into different schools at the primary school level, parents from advantaged backgrounds can exercise a greater level of choice by sending their children to private schools, for example. Predominantly, most disadvantaged children have no choice but attend disadvantaged schools with poor teaching and learning resources, and where teachers are less likely to be experienced or certificated (Clotfelter et al, 2006(Clotfelter et al, , 2010Hill et al, 2019). The evidence for selection of children from wealthy households into advantaged schools was represented by differences in educational attainment between public and private schools which are socioeconomically stratified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a multitude of studies have examined numerous teacher attributes that influence student achievement such as years of teaching experience and educational background (see Rice [2003] for review), less is known about the effects of teachers' educational and motivational beliefs and specialized content knowledge-knowledge needed to "teach" within a specific discipline-on students' academic achievement. Moreover, studies examining the effects of teachers' both educational beliefs and specialized content knowledge "collectively" on students' mathematics achievement are lacking (Hill, Charalambous, & Chin, 2018). Understanding the extent to which mathematics teaching beliefs and mathematics knowledge for teaching (MKT) play a role in students' mathematics achievement may provide some practical implications for an urban school district related to the recruitment and retention of effective teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Against the background of the aforementioned research and the increasing awareness that teachers' individual attributes afect their efectiveness and students' learning (e.g., Hill, Charalambous, & Chin, 2018;Klassen & Kim, 2017;Wayne & Youngs, 2003), the present work aims to revisit the relations between teachers' cognitive abilities and teacher efectiveness. Therefore, a systematic review of the relationship between cognitive abilities-both in a strict sense (i.e., intelligence) and proxies of cognitive abilities (i.e., college entrance scores, basic academic skills assessments)-and teacher efectiveness was conducted.…”
Section: Aims and Research Questionsmentioning
confidence: 99%